Transformações na matéria orgânica nos sedimentos e águas eutrofizados da Represa Ibirité (Ibirité-Sarzedo, MG) tratados com nitrato de cálcio em microcosmos - Colzato, Marina (Universidade Federal de São Carlos, 2010)
Due to the growing concern with the environment and the welfare of future generations the search for the restoration of degraded areas and the reestablishment of equilibrium between the anthropogenic and natural environments are nowadays highlighted. The Ibirité Reservoir (Ibirité-Sarzedo, MG) is an example of water body impacted by the disorganized urbanization and strong industrial development in the metropolitan Belo Horizonte, MG, SE Brazil. The reservoir, built by the REGAP-Petrobras in the sixties to supply water to its industrial processes, is a eutrophic water body due to the continuous contribution of urban sewage (external loading) and the consequent internal loading of nutrients (mainly of phosphorus), the primary element responsible for the eutrophication process. Among the existing technologies for the treatment of eutrophic sediment focusing on the P immobilization is the artificial supply of nitrate as an electron acceptor to the stimulation of the natural denitrification process. In this stimulation process, the different geochemical forms of reduced iron are oxidized to iron (III) oxi-hidroxides that adsorbs the phosphorus present in the sediment pore water. In addition to that, the metallic sulfides and the organic matter are oxidized as well. This work aimed at the development of laboratory experiments in a bench scale (microcosms) in which sediments and water of the Ibirité reservoir were treated with nitrate addition in order to evaluate the organic matter transformations from caused this treatment. The results indicate that there was, in the treatment microcosms, an increase in the redox potential, an almost complete abatement of the acid volatile sulfide (AVS) of the sediments, and a significant reduction of available phosphorus in the water. The UVvis spectroscopy indicated differences in the spectral profiles between the control and treatment microcosms, but uniform trends along the experiment were not identified. The elemental analysis showed agreement with the results of AVS and nitrogen species in sediment pore water data, with the reduction of sulphur and nitrogen contents.
Keywords: Química analítica; Química ambiental; Remediação; Sedimentos; Matéria orgânica; Espectroscopia de ultravioleta; Desnitrificação; Espectrocospia UV-vis; Remediation; Denitrification process; Organic matter; Sediments; UV-vis spectroscopy; CIENCIAS EXATAS E DA TERRA::QUIMICA